Dengue Virus Infection Is through a Cooperative Interaction between a Mannose Receptor and CLEC5A on Macrophage as a Multivalent Hetero-Complex - Lo, Yen-Lung; Liou, Gunn-Guang; Lyu, Jia-Huei; Hsiao, Michael; Hsu, Tsui-Ling; Wong, Chi-Huey (PloS one, 2016)
Dengue fever is a mosquito-borne viral pandemic disease that is widespread in the tropical and subtropical areas. Dengue virus uses human mannose-binding receptor (MR) and DC-SIGN on macrophages as primary receptors, and CLEC5A as signaling receptor to sense the dengue virus invasion and then to signal and stimulate macrophages to secrete cytokines. But the interplay between MR/DC-SIGN and CLEC5A is unknown. Here we demonstrate a plausible mechanism for the interaction, i.e. MR/DC-SIGN first attracts the virus with high avidity, and the virus concurrently interacts with CLEC5A in close proximity to form a multivalent hetero-complex and facilitate CLEC5A-mediated signal transduction. Our study suggests that the cooperation between a high-avidity lectin-virus interaction and a nearby low-avidity signaling receptor provides a necessary connection between binding and signaling. Understanding this mechanism may lead to the development of a new antiviral strategy.